Fenoxaprop for control of yellow bristle grass in pasture and its efficacy on other C4 grasses - James, T.K.; Rahman, A.; Dowsett, C.A.; Trolove, M.R. (New Zealand Plant Protection, 2013)
The efficacy of the herbicide fenoxaprop for control of yellow bristle grass (Setaria pumila) in pasture was evaluated in two field trials Additionally glasshouse experiments investigated its phytotoxicity on seven annual and four perennial C4 grass species Results of the field trials showed good control of yellow bristle grass and consequently a very high (up to 98) reduction in seed head production Fenoxaprop had no measurable effect on clover yield but the removal of yellow bristle grass resulted in higher production of perennial ryegrass (Lolium perenne) Fenoxaprop killed all the annual C4 species tested viz yellow bristle grass summer grass (Digitaria sanguinalis) witchgrass (Panicum capillare) smooth witchgrass (Panicum dichotomiflorum) barnyard grass (Echinochloa crusgalli) broom corn millet (Panicum miliaceum) and crowfoot grass (Eleusine indica) but was less effective on the perennial C4 grass species viz Indian doab (Cynodon dactylon) Kikuyu grass (Cenchrus clandestinus) Mercer grass (Paspalum distichum) and paspalum (Paspalum dilatatum)